The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.17843/rpmesp.2010.272.1463
|View full text |Cite
|
Sign up to set email alerts
|

Cansancio y somnolencia en conductores de ómnibus interprovinciales: estudio comparativo entre formalidad e informalidad

Abstract: Objetivos. Comparar los niveles de cansancio, somnolencia y sus repercusiones entre conductores formales e informales de ómnibus interprovinciales. Evaluar las condiciones laborales en ambos grupos de estudio. Materiales y métodos. Se realizó un estudio transversal comparativo con muestreo no probabilístico. Se incluyó 100 empresas de transporte terrestre, de las cuales 17 fueron formales según registros oficiales del Ministerio de Transportes y Comunicaciones (MTC), asimismo, los conductores se catalogaron co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(42 reference statements)
1
3
0
3
Order By: Relevance
“…The frequency of EDS is found to be doubled than the results obtained by Rosales Mayor 18 in Peruvian bus drivers also from the Lima-Huancayo route (27.8% versus 14.0%) in a cross-sectional study conducted between July and August 2007. The frequency of EDS is similar to that obtained by Deza-Becerra 22 in drivers of inter-provincial buses from Chiclayo (25.0%), a city on the northern coast of Peru, possibly due to similar occupational characteristics of drivers 17,22,28 . This could indicate an increase in the prevalence of EDS in informal interprovincial transport drivers, possibly due to a worsening of their working conditions linked to informality, the increased prevalence of factors associated with EDS or both conditions 29 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The frequency of EDS is found to be doubled than the results obtained by Rosales Mayor 18 in Peruvian bus drivers also from the Lima-Huancayo route (27.8% versus 14.0%) in a cross-sectional study conducted between July and August 2007. The frequency of EDS is similar to that obtained by Deza-Becerra 22 in drivers of inter-provincial buses from Chiclayo (25.0%), a city on the northern coast of Peru, possibly due to similar occupational characteristics of drivers 17,22,28 . This could indicate an increase in the prevalence of EDS in informal interprovincial transport drivers, possibly due to a worsening of their working conditions linked to informality, the increased prevalence of factors associated with EDS or both conditions 29 .…”
Section: Discussionsupporting
confidence: 84%
“…Another factor associated with EDS was seniority, which showed that those with ten or more years as drivers had a higher risk of developing EDS, which has also been reported by McCartt 12 in long-distance truck drivers in the United States of America which is explained by the increase in the level of exposure to driving. Added to this are the harmful effects of occupational stress caused by the frequency of day and night shifts that drivers undergo who may be affected by the existing informality even in companies classified as formal 17,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En la mayoría de los casos esto se presenta en los conductores, puesto que, muchas veces recorren trayectos largos tanto por el día y noche, siendo este último el que mayor cansancio provoca por la ausencia de sueño. En tal sentido, en muchas investigaciones [13] indican que la mitad de los conductores evaluados tienen menos horas de sueño en el periodo de 24 horas, es decir, mayormente conducen el vehículo durante la noche sin dormir y eso hace que sientan mayor cansancio o fatiga en la madrugada [17].…”
Section: Introductionunclassified